2021
DOI: 10.17485/ijed/v9.2021.111
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis and Forecasting of Fish and Fish Seed Production in Chhattisgarh, India

Abstract: Objectives: to study the trend and forecasting of fish & fish seed production in Chhattisgarh, India. Methods: The time-series data on fish production (in metric tonnes) and fish seed production (in lakhs) in Chhattisgarh for a period of 18 years from 2003-04 to 2020-21 was done. The Compound Growth Rates (CGR) of fish and fish seed production in Chhattisgarh was estimated by fitting a log-linear model. ARIMA model was applied for forecasting which includes the identification of model through coding under whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, Prevailing demand of fish seed is reached at more than 1400 million standards fry against of which 2880 million have been produced in 2020-21. Fisheries sector is very importance in generating of employment [6]. In Odisha state, it was observed that the maximum increasing trend was observed in the year 2019-20 followed by 2013-14 and 1999-2000 respectively (Fig.…”
Section: Fig 1 Fish Seed Production From Eastern Costal States Of Indiamentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, Prevailing demand of fish seed is reached at more than 1400 million standards fry against of which 2880 million have been produced in 2020-21. Fisheries sector is very importance in generating of employment [6]. In Odisha state, it was observed that the maximum increasing trend was observed in the year 2019-20 followed by 2013-14 and 1999-2000 respectively (Fig.…”
Section: Fig 1 Fish Seed Production From Eastern Costal States Of Indiamentioning
confidence: 89%
“…Average fish productivity from ponds and tanks was 3 tonne/ ha/year in India. In India, the top producers of freshwater fish through aquaculture are Andhra Pradesh, West Bengal [6,7]. In India, the states located in Eastern Coastal states such as Tamil Nadu, Andhra Pradesh, Odisha and West Bengal are always in lead position in fish seed production.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction of agricultural phenomenon has proved to be helpful for farmers and decision makers across the world. It has further helped to understand prevailing market situation, production [11][12][13][14] price behavior [15,16] and possible pests and disease attack if meteorological variables are changed suddenly. Moreover, Indian agriculture has massive land holding over wide variety of climate and potential to produce sufficient agricultural produce.…”
Section: Introduction and Reviewmentioning
confidence: 99%